Colour Stability in Sour Cherry Jam During Storage - Koca, Ilkay; Sule Ustun, N. (Asian Journal of Chemistry, 2010)
Nowadays, consumers prefer low-calorie foods with sugar substitutes to decrease calorie intake to control body weight and health problems such as diabetes and hypoglycemia. Reduced sugar sour cherry jam is one of these foods and rich in anthocyanins. The objectives of this study were to assess effect of storage on colour stability of reduced calorie sour cherry jam. The samples were stored at room temperature (20 ºC) and refrigerator temperatures (4 ºC) for 8 months. Results showed that during storage period, changes in L, b, total anthocyanin, colour density, pH and total acidity were significant (p < 0.05). The effects of storage temperature on total anthocyanin, pH, total acidity and a value were also significant (p < 0.05). Average total anthocyanin decrease of the samples stored at room temperature and refrigerator temperature were 15.74 and 6.91 %, respectively. Total anthocyanin content decreased ca. 28.21 % after 8 months of storage.